2017
DOI: 10.3310/eme04020
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of ketamine augmentation of electroconvulsive therapy to improve neuropsychological and clinical outcomes in depression (Ketamine-ECT study)

Abstract: BackgroundElectroconvulsive therapy (ECT) is the most effective acute treatment for severe depression, but there are concerns about its adverse cognitive effects. ECT may impair cognition through stimulation of glutamate receptors, and preliminary evidence has suggested that ketamine, a glutamate antagonist, may alleviate these effects. Ketamine has been shown to have a rapid, but temporary, antidepressant effect after a single infusion.ObjectiveTo determine the efficacy and safety of adjunctive low-dose ketam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 163 publications
1
9
0
1
Order By: Relevance
“…The neuropsychological assessment consisted of tests involving verbal and visual memory, attention and verbal fluency/executive function (Anderson et al, 2017a(Anderson et al, , 2017b with the key outcomes reported here.…”
Section: Assessmentsmentioning
confidence: 99%
“…The neuropsychological assessment consisted of tests involving verbal and visual memory, attention and verbal fluency/executive function (Anderson et al, 2017a(Anderson et al, , 2017b with the key outcomes reported here.…”
Section: Assessmentsmentioning
confidence: 99%
“… 9 When combined with barbiturates such as thiopental, ketamine has not been shown to be effective in reducing depressive symptoms, likely due to the effects of barbiturates in attenuating seizures as a result of their anticonvulsant properties. 7 , 11 , 15 , 16 Ketamine may have a role as an adjunctive agent to a non-barbiturate anesthetic, or as a sole anesthetic to accelerate response in the severely ill and those at risk of suicide. While iv ketamine remains the main route of administration, a few studies have demonstrated promising results in non-ECT settings when using alternate routes, notably intranasal.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that most of these adverse effects are transient in nature, and subside shortly after completion of an ECT session. 7 , 15 , 18 Therefore, an individual risk–benefit analysis should be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with multiple ECT sessions (≥2 times) were excluded. [33][34][35][36][37][38][39][40][41][42][43][44][45][46] Observational studies, conference articles, case report/ series and meta-analyses and systematic reviews were excluded. Moreover, multiple-intervention studies, including ECT combined with acupuncture or Chinese herbal medicine, were excluded.…”
Section: Eligibility Criteriamentioning
confidence: 99%